2016
DOI: 10.1149/07510.0189ecst
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Gate Electrode Configuration of IGZO TFTs for Improved Channel Control and Suppression of Bias-Stress Induced Instability

Abstract: This work presents an investigation on TFTs which have been fabricated with very similar process flows with the exception of the placement of the gate electrode. Bottom-gate TFTs with back-channel passivation that demonstrate good performance and resistance to aging have been realized, however bias-stress stability continues to remain a challenge. Top-gate TFTs have demonstrated improvement in the uniformity of device operation as well as bias-stress stability, and have the potential to offer an advantage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As shown below in Figure a, the linear and saturation transfer characteristics of printed TFTs on 200 nm thick AlO x dielectrics have steep turn on (subthreshold slope < 150 mV/dec) and show minimal counter-clockwise hysteresis (<50 mV). Additionally, the well-matched turn-on voltage ( V on ) for the linear and saturation regimes indicates the lack of any DIBL-like behavior . These characteristics suggest that the integration of InO x with UV-annealed AlO x is a favorable combination for producing a superior semiconductor to the dielectric interface, leading to well-behaved, stable device characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…As shown below in Figure a, the linear and saturation transfer characteristics of printed TFTs on 200 nm thick AlO x dielectrics have steep turn on (subthreshold slope < 150 mV/dec) and show minimal counter-clockwise hysteresis (<50 mV). Additionally, the well-matched turn-on voltage ( V on ) for the linear and saturation regimes indicates the lack of any DIBL-like behavior . These characteristics suggest that the integration of InO x with UV-annealed AlO x is a favorable combination for producing a superior semiconductor to the dielectric interface, leading to well-behaved, stable device characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, without any degradation of electrical properties such as subthreshold swing or on–off ratio, the parallel shift of V th implies the simple charge trapping between the channel and insulator is associated with device instability. Furthermore, in most of the previous studies of the instability of a-IGZO TFTs under positive bias stress, it has been concluded that electron trapping at the interface and/or in the bulk region of the insulator is the mechanism responsible for a threshold voltage shift (∆ V th ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In this study, ambient effects were excluded for the origin of bias stress instability by existence of the passivation layer.…”
Section: Resultsmentioning
confidence: 99%
“…Additional TFTs that included different G ox thickness, anneal recipes, back-channel passivation, and a double-gate (DG) electrode configuration were also used for both TCAD and model comparisons. Details of device fabrication can be found elsewhere (5,12). Long-channel devices were initially used to suppress SCE and avoid confounding between SCE and the influence of BTS.…”
Section: Model Developmentmentioning
confidence: 99%